Manifestações culturais LGBTQIA+ entre resistências, subversões e estados : estudo de caso da promoção de políticas públicas culturais LGBTQIA+ através de ações afirmativas em Mato Grosso - Barbosa, Bruna Magalhães (2023)
This study questions: what forms of promotion of LGBTQIA+ cultural expressions through affirmative actions are carried out in the State System of Culture of Mato Grosso? In this sense, this paper aims to analyze Affirmative Actions - considering absences, presences and content as ways of promoting LGBTQIA+ Cultural Public Policies in Mato Grosso and discontinuity actions with the purposes of the Colonial Nation-State, public notices carried out by Secel are analyzed -MT between the years 2016 to 2020. To do so, it has the following specific objectives: to understand the arrangements that make possible the constitutions of the Modernity/Coloniality world system and its categories of Colonial-Nation-State with implications for the Colonial Modern Gender System and Cisnormativity; to understand the arrangements that make possible the constitution of Lesbian, Gay, Bisexual, Trans, Queer, Intersex, Asexual and other Gender and Sexuality Dissident People-Bodies-Practices as categories that can resist and subvert colonial identities through cultural expressions; Discuss concepts of Public Policies, Affirmative Actions, Quota System; LGBTQIA+ Cultural Public Policies as means of contrasting analysis, through the theoretical framework adopted, the data collected and processed regarding documentary research, hypotheses and results. The applied methodology was qualitative, through case study techniques and strategies, bibliographic review, collection of documentary data, subdivided into official documents, semi-structured interviews and questionnaires. For data treatment, Content Analysis and Thematic Analysis techniques were used. The Theoretical Reference that supports the proposals is found in Decolonial Studies, Postcolonial Studies, Black Feminisms, Queer Theory and Transfeminisms. As a result, I present the still sensitive movement in the promotion of LGBTQIA+ cultural expressions through affirmative actions, but which articulates different forms of affirmative actions, sometimes combined, in different selections that allow for different ways of leveraging LGBTQIA+ cultural expressions in Brazil.